130k views
4 votes
How do u solve this

How do u solve this-example-1

2 Answers

4 votes

Solve the following:

(P). 2(5t + 8 ) + 9(2t + 1 )

Solution ======> 28t + 25

Steps:

2(5t + 8 ) + 9(2t + 1 )

Expand 2(5t + 8 ): 10t + 16

10 + 16 + 9( 2t + 1 )

Expand 9(2t + 1 ): 18t + 9

10t + 16 + 18t + 9

Simplify:

10t + 16 + 18t + 9 ========> answer: 28t + 25





K.). 1 + 7 (4 + 3t ) + 5 (12 + t ) =====> 26t + 89

Let's simplify step-by-step.

1 + 7(4 + 3t) + 5(12 + t)

Distribute:

= 1 +(7)(4) + (7)(3t) + (5)(12) + (5)(t)

= 1 + 28 + 21t + 60 + 5t

Combine Like Terms:

= 1 + 28 + 21t + 60 + 5t

= (21t + 5t) + (1 + 28 + 60)

= 26t + 89

Answer:

= 26t + 89



V.). 4 (6t + 5 ) + 9t + 3 (4t + 7 ) =====> 45t + 41

Let's simplify step-by-step.

4(6t + 5) + 9t + 3(4t + 7)

Distribute:

= (4)(6t) + (4)(5) + 9t + (3)(4t) + (3)(7)

= 24t + 20 + 9t + 12t + 21

Combine Like Terms:

= 24t + 20 + 9t + 12t + 21

= (24t + 9t + 12t) + (20+21)

= 45t + 41

Answer:

= 45t + 41





N.). t (t + 8 ) + 5 (t^2 + 6 ) =====> 6t^2 + 8t + 30

Let's simplify step-by-step.

t(t + 8) + 5(t^2 + 6)

Distribute:

= (t)(t) + (t)(8) + (5)(t^2) + (5)(6)

= t2 + 8t + 5t^2 + 30

Combine Like Terms:

= t^2 + 8t + 5t^2 + 30

= (t^2 + 5t^2) + (8t) + (30)

= 6t^2 + 8t + 30

Answer:

= 6t^2 + 8t + 30




F.). 6 (6t^2 + 7t ) + 2 (5t + 16 ) ======> 36t^2 + 52t + 32

Steps:

6 (6t^2 + 7t ) + 2 (5t + 16 )

Expand:

6(6t^2 + 7t ): 36t^2 + 42t

36t^2 + 42t + 2 (5t + 16 )

Expand:

2 (5t + 16 ): 10t + 32

36t^2 + 42t + 10t + 32

Add Similar Elements:

42t + 10t = 52t

Answer =======> 36t^2 + 52t + 32




L.). 3t^2 + t (4t + w ) + 8tw + ????????????????

Cant see the rest of the Equation.......??????




Hope that helps!!!! : )






User Kaza
by
5.8k points
2 votes

t(t + 8) + 5(t^2 + 6)

  • Distribute t inside the parentheses.

t^2 + 8t + 5(t^2 + 6)

  • Distribute 5 inside the parentheses.

t^2 + 8t + 5t^2 + 30

  • Combine like terms.

6t^2 + 8t + 30

User Bill Sambrone
by
4.8k points